O-2-17. Influence of different types of orthoses on muscle synergy control during gait in stroke patients with hemiparesis. Issue 5 (May 2018) - Wakida, Masanori; Mori, Kimihiko; Chujo, Yuta; Hirooka, Eiko; Kim, Gwang-ho; Ohata, Koji; Hase, Kimitaka
Abstract : The purpose of this study was to verify the influence of lower limb orthoses on muscle synergy control during gait in stroke patients with hemiparesis. In four subjects with acute stroke, surface EMG signals from eight muscles of the paretic lower limb were measured during gait in two conditions (ankle foot orthosis; AFO or knee ankle foot orthosis; KAFO). The number of modules, muscle weightings and activation timing profile of each module were analyzed using non-negative matrix factorization. In two subjects (Fugl Meyer Assessment; FMA > 20) who walked with mild assistance, three modules were identified during gait with KAFO, whereas two modules were identified with AFO. The third module was composed of triceps surae activities in the late stance phase of the gait cycle. In two subjects (FMA < 20) who required heavy assistance, the number of modules did not change, while muscle weightings and activation timing profile did change, corresponding to the different orthoses. These results indicated that an intervention, according to the change of muscle synergy control, is needed for stroke patients undergoing acute orthotic therapy.